Perioperative Hypertension Etiologies in Patients Undergoing Noncardiac Surgery in University Health Network Hospitals–Canada from 2015–2020 - Mohseni S; Behnam-Roudsari S; Tarbiat M; Shaker P; Shivaie S; Shafiee MA (Integrated Blood Pressure Control, 2022)
Sana Mohseni,1 Sahar Behnam-Roudsari,1 Mohammad Tarbiat,1 Pouyan Shaker,2 Seyedmohammadshahab Shivaie,1 Mohammad A Shafiee1 1Division of General Internal Medicine, Department of Medicine, Toronto General Hospital, Toronto, ON M2G 2C4, Canada; 2College of Medicine, Kansas City University, Kansas City, MO, USACorrespondence: Mohammad A Shafiee, Division of General Internal Medicine, Department of Medicine, Toronto General Hospital, 200 Elizabeth Street, 14 EN-208, Toronto, ON M5G 2C4, Canada, Tel +1 416-340-4800 ext 6244, Fax +1 416-595-5826, Email mohammad.shafiee@uhn.caIntroduction: Perioperative hypertension, defined as increased blood pressure around the surgery, is a known risk factor for perioperative complications, including cardiovascular events. Identifying reasons associated with hypertension in each period is of great help in preventing and better managing perioperative hypertension.Objective: The aim of the study was to explore common etiologies of hypertension during the perioperative period (pre, intra, and post-operation) in patients who underwent noncardiac surgeries in University Health Network (UHN) hospitals, Canada, from 2015 to 2020.Patients and Methods: We retrospectively analyzed the medical records of 174 patients undergoing noncardiac surgeries who experienced perioperative hypertension. We assessed the prevalence of 10 reasons for perioperative hypertension as a whole and also each period separately according to the physicians’ notes in patients’ medical records. Two-way measurements ANOVA was used to determine the change of mean hypertension among patients for specific etiology.Results: The common etiologies of perioperative hypertension were poorly controlled hypertension (21.8%), excessive fluid therapy (19.5%), excessive vasopressor (18.4%), and medication withdrawal (13.7%). Regarding each period separately, the most common reasons were poorly controlled hypertension for pre (42.9%) and intraoperative period (22.7%) and fluid overload for the postoperative period (20.1%). Poor control of hypertension showed both within-subject statistical significance for systolic and between-subject statistical significance for diastolic blood pressure.Conclusion: Poorly controlled hypertension is the most significant etiology of perioperative hypertension in patients undergoing noncardiac surgeries. Apart from poorly controlled hypertension, as a patient-related factor, iatrogenic factors such as excessive vasopressor therapy, aggressive fluid replacement and poor management of antihypertensive medications can also cause perioperative hypertension.Keywords: hypertension, intraoperative, perioperative, postoperative, surgery